2020
DOI: 10.1039/d0ra01710h
|View full text |Cite
|
Sign up to set email alerts
|

Solventless synthesis of cerium oxide nanoparticles and their application in UV protective clear coatings

Abstract: Solventless synthesis of metal oxide nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…It can be observed that the crystallite size increased when the preparation of cerium oxide nanoparticles was made at room temperature and in the presence of NH 4 OH as precipitating agent instead of NaOH. Using the Miller indices for the (111) plane, the lattice constant, a, can be estimated by the relation (1). The calculated values of the lattice constant are given in Table 1.…”
Section: X-ray Diffraction Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that the crystallite size increased when the preparation of cerium oxide nanoparticles was made at room temperature and in the presence of NH 4 OH as precipitating agent instead of NaOH. Using the Miller indices for the (111) plane, the lattice constant, a, can be estimated by the relation (1). The calculated values of the lattice constant are given in Table 1.…”
Section: X-ray Diffraction Investigationmentioning
confidence: 99%
“…Some properties, such as quantum confinement as well as high surface-to-volume ratio, induced by the nanosized dimensions of the cerium oxide, together with the low redox potential of the Ce 4+ /Ce 3+ couple, determine heterogeneous processes at the nanoparticle surface in contact with air or liquid. Industrial applications of the materials based on cerium oxide nanoparticles include UV protective materials [1], oxygen sensor and storage [2,3], catalysis [4,5], and solid oxide fuel cells [6,7]. Reversible redox reaction of the Ce 4+ /Ce 3+ couple determines the pro-or antioxidant properties of cerium oxide nanomaterials with potential utilizations in medicine, playing a dual role as a cell protector against oxidative stress, but also as a sensitizer in cancer radiotherapy or in antibacterial applications [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Here, morphology (size, shape, distribution) of nanoceria growth is built by a nucleation dissolution recrystallization step mechanism, depending on the reaction time. 48 Fig. 6A and B show nanoceria with average size of 2 nm formed 0.7 h decomposition time.…”
Section: Characterization Studiesmentioning
confidence: 96%
“…The decomposed product was dissolved in hexane and sonicated gently to produce colloidal ceria nanoparticles. 48 The nanocrystallite cerium oxide powders were also prepared from precursor nanopowders by thermal decomposition. The Ce-propionate powder precursor was prepared by dissolved cerium( iii ) acetate sesquihydrate in the methanol : propionic acid (with a 1 : 2 ratio), stirring at 60 °C, then dried at 120 °C in air.…”
Section: Synthesis Of Nanoceriamentioning
confidence: 99%
“…Here, "∞" can be set as any large number on the calculations without direct impact on the potential values since C = 0 for the M -M interactions. 42 To achieve our goals, we considered two particles size, namely, 500 and 864 cations with the appropriate number of oxygen anions, which yields oxide particles with diameters similar with experimental observations, 43,44 which are large enough to show ordered core region, internal nucleation, and domain walls. Systems with that size are not affordable by ab initio MD calculations, and hence, all MD simulations were based on atomistic force field simulations, as described below.…”
Section: Theoretical Approach and Computational Detailsmentioning
confidence: 99%